Posterior Ankle Impingement Syndrome: An Updated Review of Outcomes, Treatments, and Techniques - Shu Lin BS; Paul Fine-Lease BS; Taylor Wingo MD; Arianna Gianakos DO (Foot & Ankle Orthopaedics, 2024)
Category: Arthroscopy; Ankle Introduction/Purpose: Posterior ankle impingement syndrome (PAIS) is a common athletic injury, often associated in sports with repetitive ankle plantar flexion movements. The purpose of this study was to conduct a systematic review to evaluate the management and outcomes of patients with PAIS with focus on emerging operative techniques. Methods: A literature search was conducted using PubMed and Cochrane databases from within ten years from July 2013 to July 2023 in accordance with the 2020 Preferred Reporting Items for Systematic Review and Meta-Analysis guidelines. Inclusion criteria consisted of all clinical studies evaluating posterior ankle impingement within the last ten years. Outcome measures included the following: visual analogue scale for pain (VAS), the American Orthopaedic Foot & Ankle Society Ankle-hindfoot score (AOFAS), return to sport time, and complication rates. Results: Nine studies evaluating 270 patients with a mean age of 24.7 years (mean range, 11.6-31.75 years) met inclusion criteria. Four studies were retrospective comparative studies evaluating open versus arthroscopic intervention. Five were case series, two evaluated open techniques, and three evaluated arthroscopic techniques. All studies that evaluated VAS pain and AOFAS clinical outcome scores reported improvements post-operatively for both groups. The return to sport ranges from 11.5 to 14.9 weeks with open treatment and 6.2 to 23.9 weeks with arthroscopic intervention. Arthroscopic group had six reported complications (2.83%), with infection and dysesthesia being the most reported. Open group also reported six complications (10.3%) with infection and sural nerve complications being the most commonly reported. Table 1 describes technical tips from each of the included studies. Conclusion: This study demonstrated that arthroscopic intervention for PAIS may result in quicker return to sports with lower rates of complications when compared with open excision and debridement. There are a variety of techniques utilized in order to afford ease and efficiency with minimally invasive arthroscopic strategies for PAIS. Future research including randomized controlled trials would be beneficial in order to clarify benefits of arthroscopic treatment of PAIS.